TROY Modulates Cancer Stem-Like Cell Properties and Gefitinib Resistance Through EMT Signaling in Non–Small Cell Lung Cancer - Wu, Linying; Yu, Yuman; Xu, Liming; Wang, Xiaoling; Zhou, Jianying; Wang, Yuehong (Frontiers in Genetics, 2022)
Targeted therapy has made breakthrough progress in the treatment of advanced non-small cell lung cancer (NSCLC) in recent 20 years. Despite that, acquired resistance of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) is an urgent clinical problem. Our study established an acquired gefitinib-resistant cell line, which exhibited epithelial-mesenchymal transition (EMT) and stem cell-like properties. Transcriptional sequencing and bioinformatics analysis revealed that TROY was significantly increased in gefitinib-resistant cells. Gene set enrichment analysis (GSEA) showed EMT was the core enriched hallmark in the resistant cells. TROY siRNA interference could overcome the gefitinib resistance with the down-regulated expression of EMT and CSCs markers. What’s more, immunohistochemistry indicated TROY overexpressed in tumor samples from patients acquired resistance to first-generation EGFR-TKI without T790M mutation. And the expression of TROY was associated with poor prognosis in LUAD. Here we provided the potential role of TROY in the resistance of targeted therapy and a new strategy to overcome the acquired resistance to EGFR-TKI in NSCLC.